Handbook of the Clinical Psychology of Ageing 2008
DOI: 10.1002/9780470773185.ch32
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Family Caregivers of People with Dementia

Abstract: Family caregivers of people with dementia, often called the invisible second patients, are critical to the quality of life of the care recipients. The effects of being a family caregiver, though sometimes positive, are generally negative, with high rates of burden and psychological morbidity as well as social isolation, physical ill-health, and financial hardship. Caregivers vulnerable to adverse effects can be identified, as can factors which ameliorate or exacerbate burden and strain. Psychosocial interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
328
5
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(363 citation statements)
references
References 74 publications
13
328
5
17
Order By: Relevance
“…A low educational level, greater social resources, social participation, and adequate health conditions can all positively contribute to the rendering of care for a dependent patient (26) . In many situations, the lack of a job outside the household, due to a low academic background, leads caregivers to taking care of the patient and, despite difficulties, leads to satisfaction for being able to contribute to the treatment of a sick family member.…”
Section: Discussionmentioning
confidence: 99%
“…A low educational level, greater social resources, social participation, and adequate health conditions can all positively contribute to the rendering of care for a dependent patient (26) . In many situations, the lack of a job outside the household, due to a low academic background, leads caregivers to taking care of the patient and, despite difficulties, leads to satisfaction for being able to contribute to the treatment of a sick family member.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that caregivers have a need for education on dementia as well as a need for support services and information on care [9]. Researchers also suggest that there is a need for information about services and support groups for the person diagnosed with dementia in addition to the family [9,12].…”
Section: Family Knowledge Of Alzheimer's Diseasementioning
confidence: 99%
“…Caregivers of persons with dementia had a higher level of unmet needs for formal services and faced more barriers in accessing services when compared to other caregivers of chronically ill patients (Harmell et al, 2011;Stirling et al, 2010). However, much of the research on dementia caregivers is centered on psychological well-being such as stress, depression, and anxiety (Brodaty & Donkin, 2009;Gaugler et al, 2008;Harmell et al, 2011, Takai et al, 2011. Although there is evidence to suggest that an increase in caregiver's mastery and self-efficacy leads to better coping, which in turn has a protective effect on their well-being (Harmell et al, 2011), few studies have explored what can be done to alleviate caregiver challenges in accessing and utilizing resources that have the potential to improve quality of life for both persons with dementia and their family caregivers.…”
mentioning
confidence: 99%